Impact of pharmacist-led intervention in medication adherence and inhaler usage on asthma and chronic obstructive pulmonary disease control: a quasi-experimental study - Rasaq Adisa; Uyiose F. Ufuah; Olusoji M. Ige (BMC, 2024)
Abstract Background Despite recent advances in the management of asthma and chronic obstructive pulmonary disease (COPD), patients still experience suboptimal disease control largely due to medication non-adherence and inappropriate use of inhaler. This study evaluates the impact of pharmacist-led intervention in medication adherence and inhaler usage on asthma and COPD control among out-patients attending the premier tertiary hospital in Nigeria. Method A quasi-experimental study carried-out among eligible out-patients attending pulmonology clinic of University College Hospital, Ibadan. Baseline questionnaire explored medication adherence using a comprehensive-medication-adherence-assessment-scale (CMAAS-12) developed by the study co-investigators, use of pressurized-metered-dose (pMDI) and Diskus inhalers, as well as asthma/COPD control using validated asthma control test (ACT) and COPD assessment test (CAT). Subsequently, patients were allocated into control (n = 65) or intervention group (n = 65) using odd or even number. Intervention group received 2-month follow-up educational and/or cognitive-behavioural interventions to resolve identified adherence barriers, while control group continued with traditional care. Descriptive statistics, Chi-square and Wilcoxon-signed-ranked tests were used for analysis at p < 0.05. Results Overall, patients with optimal adherence were 11(18.6%) and 16(27.1%), p = 0.132 (control), but 20(33.3%) and 38(63.3%), p < 0.001 (intervention) at baseline and post-baseline, respectively. Specifically, in the intervention group, the identified adherence barriers at baseline were summarized into knowledge (120;40.4%), practical (115;38.7%) and attitudinal (62;20.9%). Patients with correct use of pMDI were 11(21.6%) baseline and 19(36.5%) post-baseline, p = 0.011 (control), but 13(22.8%) and 46(80.7%) respectively, p < 0.001 (intervention). Correct use of Diskus inhaler were 5(50.0%) and 4(40.0%), p = 0.157 (control), but 7(35.0%) and 14(70.0%), p = 0.025 (intervention) at baseline and post-baseline, respectively. Patients with 'well-controlled asthma' were 25(44.6%) and 26 (47.3%), p = 0.025 (control), but 18(35.3%) and 32(60.4%), p < 0.001 (intervention) at baseline and post-baseline, respectively. The COPD-specific health status indicated that 0(0.0%) and 1(14.3%), p = 0.059 (control), but 0(0.0%) and 7(50.0%), p < 0.001 (intervention) at baseline and post-baseline, respectively, belonged to 'low COPD impact'. Conclusion Pharmacist-led intervention significantly enhanced medication adherence and appropriate use of inhaler among the intervention cohort, with subsequent significant improvement in asthma control and reduced COPD impact compared with the control group. This underscores the need for active involvement of pharmacists in collaborative management of patients with chronic respiratory diseases in clinical practice. Trial registration ClinicalTrials.gov identifier: NCT06417931. Retrospectively-registered.